Nitidulidae (Coleoptera) Associados A Frutos de Café (Coffea Arabica L.) - Fernandes, Daniell Rodrigo Rodrigues [UNESP]; Bená, Daniela de Cassia; Lara, Rogéria Inês Rosa; Ide, Sergio; Perioto, Nelson Wanderley (My University, 2012)
This study reports sap beetles from fruits of a coffee crop in Cravinhos, SP, Brazil. Fruits were collected directly from plants and, in laboratory, from the fruits at the cherry state we obtained 20 adults of three species: Carpophilus nepos Murray, 1864, Colopterus niger Murray, 1864 and Nitops sordidus Erichson, 1847. This is the first report of association between these insects and coffee fruits.
Sap beetles (Coleoptera: Nitidulidae) in coffee fruits (Coffea arabica L.)
Keywords: Agroecosystem; Carpophilus nepos; Colopterus niger; Nitops sordidus